75 best business practices for socially responsible companies - Reder, Alan (G. P. Putman's Sons, 1995)
Any forward-looking corporate leader or entrepreneur will want to know about these innovative ideas and how to implement them. Because these practices sprang from some of America's most creative business minds, each reflects profound business sense as well as social concern.